Microbiological and chemical characteristics of porkfish inasua, traditional fish fermented from Maluku, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Mahulette F. 2023. Microbiological and chemical characteristics of porkfish inasua, traditional fish fermented from Maluku, Indonesia. Biodiversitas 25: 1-8. Porkfish inasua consisted of two types, i.e., with and without coconut sap. The research aimed to analyze the microbiological and chemical characteristics of two types of porkfish inasua. The microbiological characteristics are used to determine the role of microbes and product safety whereas the chemical characteristics, including proximate composition, amino acids, and fatty acids contents can determine the nutritional value for consumption. The sample of porkfish inasua was taken from traditional producers in Layeni, Teon, Nila, and Serua (TNS) Islands, Maluku, Indonesia. The microbiological analysis was done using the plate count method. From the measurement, the total number of halotolerant and coliform bacterial in porkfish inasua without sap were 6.2 log cfu/g and 6.1 log cfu/g, respectively. In comparison, the total of Bacillus and related genera in porkfish inasua with sap was 5.9 log cfu/g at the end of fermentation. The fat content of both types of inasua was around 17%. The total amino acids and fatty acids contents of porkfish inasua without sap at the end of fermentation were 15.31 and 57.08%, while porkfish inasua with sap were 15.85 and 63.81%, respectively. The dominant bacteria found in porkfish inasua without sap was Staphylococcus saprophyticus, while porkfish inasua with sap was Bacillus cereus. These two bacteria play a role in fermentation so porkfish inasua was safe for consumption. Generally, chemical characteristics of porkfish inasua with sap were better than those of porkfish inasua without sap, but statistically, it was not significantly different. This research can improve the quality of porkfish inasua as local fermented fish products in Maluku.
Keywords: Coconut sap, fish fermented, porkfish, proximate composition, wax ester